Enhancing Business Management Students' English Vocabulary through Quizlet: Exploring Classroom Action Research - Wulandari, Mega Fitri; Irfiani , Bakri (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
The study aims to investigate the effectiveness of MALL application using in the classroom. One of Mobile Assisted Language Learning (MALL) application used is Quizlet. The study employs a Classroom Action Research approach to assess the impact of Quizlet on third semester of Business Management students' vocabulary mastery. The data collection techniques in this research are observation and test. The result of this research show that MALL/ Quizlet contribute to a substantial improvement in vocabulary test scores and leading students to enhance their vocabulary proficiency. The use of technology-based tools like Quizlet not only facilitated self learning but also improved pronunciation and contextual usage of words. The accessibility of devices like stability of internet connections, students self motivation, and effective supervision emerged as critical element impacting the efficiency of Mobile Assisted Language Learning (MALL), particularly the utilization of Quizlet for enhancing vocabulary mastery.